2008
DOI: 10.1086/527030
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Infrared Spectral Diagnosis of Submillimeter Galaxies

Abstract: We present deep mid-IR spectroscopy with Spitzer of 13 SMGs in the GOODS-N field. We find strong PAH emission in all of our targets, which allows us to measure mid-IR spectroscopic redshifts and place constraints on the contribution from star formation and AGN activity to the mid-IR emission. In the high-S/ N composite spectrum, we find that the hot dust continuum from an AGN contributes at most 30% of the mid-IR luminosity. Individually, only 2/13 SMGs have continuum emission dominating the mid-IR luminosity;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
732
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 376 publications
(788 citation statements)
references
References 82 publications
(185 reference statements)
49
732
7
Order By: Relevance
“…This figure highlights the expected change in observed flux density with redshift for a template DSFG SED of fixed luminosity (Pope et al, 2008b) across many observed-frame wavelengths, from the optical (i-band, 0.8µm) through the near-IR, mid-IR, far-IR, millimeter, and the radio (1.4 GHz). The K-correction at 250 < λ < 500 µm is still negative, though is far less dramatic than the very negative K-correction at ∼1 mm and the very positive K-correction at optical/near-infrared and radio wavelengths which causes a dramatic drop in redshift flux density.…”
Section: The Very Negative K-correctionmentioning
confidence: 52%
See 4 more Smart Citations
“…This figure highlights the expected change in observed flux density with redshift for a template DSFG SED of fixed luminosity (Pope et al, 2008b) across many observed-frame wavelengths, from the optical (i-band, 0.8µm) through the near-IR, mid-IR, far-IR, millimeter, and the radio (1.4 GHz). The K-correction at 250 < λ < 500 µm is still negative, though is far less dramatic than the very negative K-correction at ∼1 mm and the very positive K-correction at optical/near-infrared and radio wavelengths which causes a dramatic drop in redshift flux density.…”
Section: The Very Negative K-correctionmentioning
confidence: 52%
“…The timing was perfect for investigating the mid-infrared spectral properties of 850µm-selected SMGs, now described in Menéndez-Delmestre et al (2007), Valiante et al (2007), Pope et al (2008b) and Menéndez-Delmestre et al (2009). These works find that SMGs have a majority of broad PAH emission features (80%) with the remaining 20% of SMGs being dominated in the mid-IR by AGN.…”
Section: Mid-infrared Diagnosticsmentioning
confidence: 93%
See 3 more Smart Citations